Consumer perception of “artificial meat” in the educated young and urban population of Africa - Kombolo Ngah, Moïse; Chriki, Sghaier; Ellies-Oury, Marie-Pierre; Liu, Jingjing; Hocquette, Jean-François (Frontiers in Nutrition, 2023)
African’s population is expected to grow especially in cities to reach about 2.5 billion in 2050. This will create an unprecedented boom in the demand for animal-based food over the coming years which will need to be managed properly. Industry stakeholders worldwide have been touting the potential benefits of “artificial meat” in recent years as a more sustainable way of producing animal protein. “Artificial meat” is therefore moving into the global spotlight and this study aimed to investigate how African meat consumers of the coming generations perceive it, i.e. the urban, more educated and younger consumers. Three surveys were conducted with more than 12 000 respondents in total. The respondents came from 12 different countries (Cameroon, Congo, -DRC Democratic Republic of Congo, Ghana, Ivory Coast, Kenya, Morocco, Nigeria, Senegal South Africa, Tanzania and Tunisia). “Artificial meat” proved to be fairly well known in the surveyed countries as about 64% the respondents had already heard of “artificial meat”. Only 8.9% were definitely willing to try “artificial meat” (score of 5 on a scale of 1-5) mostly males between 31 and 50 years of age. Furthermore, 31.2% strongly agreed that “artificial meat” will have a negative impact on the rural life (score of 5 on a scale of 1-5) and 32.9% were not prepared to accept “artificial meat” as a viable alternative in the future but were still prepared to eat meat alternatives. Of all the results, we observed significant differences in responses between respondents' countries of origin, age and education level with interactions between these factors for willingness to try. For instance, the richest and most educated countries that were surveyed tended to be more willing to try “artificial meat”. A similar pattern was observed for willingness to pay, except that gender had no significant effect and age had only a small effect. One major observation is that a large majority of consumers are not willing to pay more for “artificial meat” than for meat from livestock.